Developing Product-Service Systemswith InnoFunc® - Wagner, Lena; Baureis, David; Warschat, Joachim (International Journal of Industrial Engineering and Management, 2013)
In times of globalization and saturated markets, requirements change significantly. A possibility to adapt to this can be found in the integration of products and services into so called Product-Service Systems (PSS). Migrating from a manufacturing company to a solutionprovider raises different challenges though, especially in the early phases of product development. The strategic question if animplementation of PSSis an appropriate step for a company has to be evaluated carefully. Therefore it is necessary to approximate this problem with a well-defined holistic approachwhich includes not only generating ideas but also identifying the needed competences. This paper introducesthe InnoFunc®-approach for developing PSSsuccessfully in the early phases and identifying the needed competences. Article history: Received (26 April 2012); Revised (09December 2012); Accepted (16 January 2013)